Visual Recognition of Combined Stimuli - Y A Chudina; D A Shlyakhta (Peoples' Friendship University of Russia (RUDN University), 2014)
The article submits the results of the experimental research of the subjective discrimination of combined stimuli, characterized by the changes of the spectral composition of the radiation, light intensity and tilt angle of the object in the visual field. The received data were interpreted in terms of vector approach and modular conception of visual perception according to which the visual perception is carried out with the help of the similar type sensory modules of visual system detecting different characteristics of the stimuli. The result of the integration of the sensor modules is a multichannel neuron network, represented in the form of the multidimensional geometrical spherical space.